Cost‐effectiveness Analysis Appraisal and Application: An Emergency Medicine Perspective. (11th May 2017) - April, Michael D.; Murray, Brian P.
Abstract: Cost‐effectiveness is an important goal for emergency care delivery. The many diagnostic, treatment, and disposition decisions made in the emergency department (ED) have a significant impact upon healthcare resource utilization. Cost‐effectiveness analysis (CEA) is an analytic tool to optimize these resource allocation decisions through the systematic comparison of costs and effects of alternative healthcare decisions. Yet few emergency medicine leaders and policymakers have any formal training in CEA methodology. This paper provides an introduction to the interpretation and use of CEA with a focus on application to emergency medicine problems and settings. It applies a previously published CEA to the hypothetical case of a patient presenting to the ED with chest pain who requires risk stratification. This paper uses a widely cited checklist to appraise the CEA. This checklist serves as a vehicle for presenting basic CEA terminology and concepts. General topics of focus include measurement of costs and outcomes, incremental analysis, and sensitivity analysis. Integrated throughout the paper are recommendations for good CEA practice with emphasis on the guidelines published by the U.S. Panel on Cost‐Effectiveness in Health and Medicine. Unique challenges for emergency medicine CEAs discussed include the projection of long‐term outcomes from emergent interventions, costing ED services, and applying study results to diverse patient populations across various ED settings. The discussion also includes an overview of the limitations inherent in applying CEA results to clinical practice to include the lack of incorporation of noncost considerations in CEA (e.g., ethics). After reading this article, emergency medicine leaders and researchers will have an enhanced understanding of the basics of CEA critical appraisal and application. The paper concludes with an overview of economic evaluation resources for readers interested in conducting ED‐based economic evaluation studies.